Restrukturisasi Obyek Wisata Alam Dan Agro Sebagai Wujud Pelayanan Sosial Kemasyarakatan Di Desa Genito Kabupaten Magelang - Adhi Surya Perdana (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2019)
Tourism is now seen as a sector popular in the national economy and the world, where one of the motor industry style of contemporary capable of providing social services community, especially in the village of Genito in providing natural attractions and agro, as well as the opportunities of economic growth in terms of employment opportunities, income, the standard of living and to enable the local production sector. The purpose of this study which is to identify the factors driving and inhibiting natural attractions as well as the restructuring and agro tourism. Problems include the lack of accessibility of land and the difficulty of the motor vehicle to the location of natural and agro. This is a qualitative study, which describes the study explanation about the state of the field findings and submit the questionnaire contained structured questions addressed to the public ranging from community leaders, stakeholders of the village administration, the offender driving tourism, and tourists with the total respondents as many as 30 people, using the method of random sampling incidental. The study results showed that the natural attractions and tourism in the village of Genito there are two attractions that nature tenure is owned by forestry and agricultural land supported rural communities that provide beauty agro tourism. Restructuring of natural attractions such as swimming pools, fish ponds and objects whose existence Selfie nestled in the woods with Sukorini name. Restructuring of the natural attractions in the form of a pool is an innovation village government.